2018
DOI: 10.1007/s00468-018-1669-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on the developmental rates of seedling emergence and leaf-unfolding in two dwarf bamboo species

Abstract: Key messageThe mean and variance of developmental rates of bamboos at different temperatures follow a power law. The rate isomorphy hypothesis, demonstrated in insects and mites, does not hold in bamboos. Abstract The developmental time of plants and poikilotherms can be significantly affected by temperature. Developmental rate (i.e. the reciprocal of developmental time) of arthropods and germination rate of some plant seeds have been demonstrated to follow a linear function with temperature. The rate isomorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Ballantyne and Kerkhoff (2007) suggested that individuals' reproductive correlation determines the size of b, while Kilpatrick and Ives (2003) proposed that interspecific competition could reduce the value of b. Above all, empirically, b usually lies between 1 and 2 (Maurer and Taper, 2002). However, it is expected that TPL holds with b = 2 exactly in a population with a constant coefficient of variation (CV) of population density.…”
Section: Discussionmentioning
confidence: 99%
“…Ballantyne and Kerkhoff (2007) suggested that individuals' reproductive correlation determines the size of b, while Kilpatrick and Ives (2003) proposed that interspecific competition could reduce the value of b. Above all, empirically, b usually lies between 1 and 2 (Maurer and Taper, 2002). However, it is expected that TPL holds with b = 2 exactly in a population with a constant coefficient of variation (CV) of population density.…”
Section: Discussionmentioning
confidence: 99%
“…It is also well established that development times of arthropods vary not only with temperature, but also as a function of other environmental and biotic factors such as salinity, food quality or quantity, social interactions, oxygen, pH, etc., and different combinations thereof (Anger, 1991; Klein Breteler, 1980; Klein Breteler et al, 1995; Anger, 2001; Keppel et al, 2012); the possibility that developmental proportions might vary due to such factors should also be investigated using an approach analogous to the one developed for temperature in this study. It would also likely be very useful to combined the datasets and approaches used in this study with some of those from the literature on development rate isomorphy among ectotherms (Jarošík, 2002, 2004; Shi et al, 2010; Sandhu et al, 2011; Kuang et al, 2012; Lin et al, 2018). Doing so could increase the taxonomic range over which data were collected and analyzed, and allow for these two approaches to be combined and analyzed in interesting and useful ways.…”
Section: Discussionmentioning
confidence: 99%
“…Within the present study, this form of development was termed ‘variable proportional development’ and abbreviated ‘VPD’, and models representing it were developed based on previous research on arthropod development. A number of studies have investigated the ‘rate isomorphy’ hypothesis, which proposes that relative durations of particular developmental stages are constant across temperatures, and/or that lower developmental thresholds are constant among development stages, on various ectotherm taxa, including insects, mites, and bamboos (e.g., Jarošík, 2002, 2004; Shi et al, 2010; Sandhu et al, 2011; Kuang et al, 2012; Lin et al, 2018). In these studies, development rates were proposed to increase linearly with temperature across a range of intermediate temperatures, but could potentially deviate from linearity at more extreme (low and high) temperatures approaching a species’ or stage’s thermal limits.…”
Section: Introductionmentioning
confidence: 99%
“…This result serves as a theoretical guideline for the treatment of grazing planning and the rational utilization of grassland resources. Temperature variation influences phenology through multiple pathways [61][62][63][64]. It is generally recognized that temperature increases in spring before SOS causes the effective accumulative temperature to reach seed germination and leaf unfolding ahead of time [64,65].…”
Section: Npp Response To Phenologymentioning
confidence: 99%